Correlates of HIV self-testing among female sex workers in China: implications for expanding HIV screening - Cheng Wang; Ya-Jie Wang; Joseph D. Tucker; Ming-Zhou Xiong; Hong-Yun Fu; M. Kumi Smith; Wei-Ming Tang; Jason J. Ong; He-Ping Zheng; Bin Yang (BMC, 2020)
Abstract Background Human immunodeficiency virus (HIV) self-testing may help improve test uptake among female sex workers. China has implemented many HIV self-testing programs among men who have sex with men, creating an opportunity for promotion among female sex workers. However, there is a limited literature on examining HIV self-testing among female sex workers. This study aimed to examine HIV self-testing experiences and its determinants among female sex workers in China. Methods A venue-based, cross-sectional study was conducted among Chinese female sex workers in 2019. Participants completed a survey including social-demographic characteristics, sexual behaviors, and HIV self-testing history, the distribution of which were analyzed using descriptive analysis. Multivariable logistic regression was conducted to identify associations with HIV self-testing. Results Among 1287 Chinese female sex workers, 1072 (83.3%, 95% confidence interval [CI] 81.2-85.3%) had ever tested for HIV, and 103 (8.0%, 95% CI 6.6-9.6%) had ever used HIV self-testing. More than half reported that the self-test was their first HIV test (59.2%, 61/103), around one-fifth reported HIV self-testing results influenced the price of sex (21.4%, 22/103). A minority of individuals reported ever experiencing pressure to undertake HIV self-testing (6.8%, 7/103). After adjusting for covariates, HIV self-testing was positively associated with receiving anal sex in the past month (adjusted odds ratio [aOR] = 2.2, 95% CI 1.4-3.5), using drugs before or during sex (aOR = 2.8, 95% CI 1.8-4.5), injecting drugs in the past 6 months (aOR = 2.6, 95% CI 1.2-6.0), being diagnosed with other sexually transmitted infections (aOR = 1.6, 95% CI 1.0-2.5), tested for other sexually transmitted infections in the past six months (aOR = 3.4, 95% CI 2.1-5.5), ever tested in the hospital (aOR = 3.4, 95% CI 2.0-5.6), and ever tested in the community (aOR = 1.5, 95% CI 1.2-1.9). Conclusions Our findings suggest that HIV self-testing could expand overall HIV testing uptake, increase HIV testing frequency, reach sub-groups of high-risk female sex workers and has limited potential harms among female sex workers. HIV self-testing should be incorporated among Chinese female sex workers as a complement to facility-based HIV testing services.